Grand Prize for the Best Student Presentation - Angastiniotis, Nicos (My University, 2026)
1991-1992 APMI Philadelphia Section Student Seminar: Grand Prize for the Best Student Presentation: Complimentary Attendance at the 1992 Powder Metallurgy World Congress June 21-26 San Francisco, California
Keywords: Natural sciences